2021
DOI: 10.29312/remexca.v12i5.2905
|View full text |Cite
|
Sign up to set email alerts
|

Utilización de microorganismos para una agricultura sostenible en México: consideraciones y retos

Abstract: Numerosas especies vegetales de interés agrícola establecen simbiosis con microorganismos edáficos, tal es el caso de microorganismos promotores del crecimiento vegetal; los cuales proporcionan grandes beneficios debido a que ayudan a disminuir el uso excesivo de fertilizantes y pesticidas utilizados en la producción agrícola. Actualmente, la agricultura mexicana busca alternativas de fertilización amigables con el medio ambiente. Es por ello que las prácticas de agricultura sostenible solamente pueden ser exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Therefore, it is necessary to implement strategies to improve sustainability indexes, especially economically, in order to generate greater profitability and environmentally develop technological practices such as the use of biofertilizers that are not polluting or harmful to the health of farmers and consumers. In this sense, the use of beneficial microorganisms, among which are the so-called plant growth-promoting microorganisms, which can favor their development, generate tolerance to biotic and abiotic stresses in the plant and facilitate its nutrition due to their capacity to capture atmospheric nitrogen, has become increasingly important, produce growth-promoting substances such as indoleacetic acid and solubilize inorganic phosphorus from insoluble compounds, and at the same time can antagonize phytopathogens in host plants (Cruz-Cárdenas, 2021). Several studies have demonstrated the importance of these microorganisms in potato production and quality (Sawicka et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to implement strategies to improve sustainability indexes, especially economically, in order to generate greater profitability and environmentally develop technological practices such as the use of biofertilizers that are not polluting or harmful to the health of farmers and consumers. In this sense, the use of beneficial microorganisms, among which are the so-called plant growth-promoting microorganisms, which can favor their development, generate tolerance to biotic and abiotic stresses in the plant and facilitate its nutrition due to their capacity to capture atmospheric nitrogen, has become increasingly important, produce growth-promoting substances such as indoleacetic acid and solubilize inorganic phosphorus from insoluble compounds, and at the same time can antagonize phytopathogens in host plants (Cruz-Cárdenas, 2021). Several studies have demonstrated the importance of these microorganisms in potato production and quality (Sawicka et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…La rica e intrincada relación, que tiene la producción y las operaciones en las organizaciones, plantea un conjunto de retos que podemos clasificar en; 1) retos asociados al desarrollo del mercado (Aguilar-Barceló e Higuera-Cota, 2019; Rodríguez, 2017); 2) retos asociados cambios económicos (Silva y Gómez, 2018); 3) retos asociados a factores productivos; 4) retos asociados al ambiente tecnológico (Cárdenas et al, 2021); y (5) retos asociados a los modelos de negocio emergentes (Barrientos-Felipa, 2017) tal y como se aprecia en la Figura 1.…”
Section: Introductionunclassified
“…Its great physiological adaptability is due to its capacity to produce spores [2,3]. In addition, this bacterial genus is characterized by its wide functional, metabolic and genomic diversity [4,5], and is widely used in several biotechnology applications, such as an active ingredient in the formulation of biofertilizers and bioplaguicides [6,7].…”
Section: Introductionmentioning
confidence: 99%